STUDI EMISI SPEKTRA PADA SINTESIS PEMBAKARAN METAL ALUMINIUM DALAM PLASMA-UDARA - Imam Sholahuddin; Andi Sanata (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2022)
Research on emission spectra of metal combustion at temperatures above the boiling point of Al has been successfully carried out. This method can be used as a qualitative characterization of the presence of elements or compounds involved in the combustion process. Recording of emission spectra data was carried out during the process of burning Al powder with oxygen O in an air plasma flame at atmospheric pressure. The burning characteristic of Al was detected at the peak intensity of the wavelength λAl = 396 nm, and the reaction products of AlO with the peak intensity of the wavelength λAlO were 471, 489 and 512 nm, respectively. The absolute temperature of the plasma flame black body was 5660 K based on the highest peak intensity λAlO = 512 nm. The increase in emission intensity was quite significant when Al was started to be injected at 1.25 seconds, followed by an unstable plasma form. The steady state of the plasma flame indicates a full reaction in the vapor phase of AlO(g) in the form of Al sub-oxide and alumina before condensing on the outer surface area of ​​the plasma. High temperature thermal plasma-air can increase the homogeneity of the atomization process of particles into gaseous vapor which is an important initiation where nanoscale AlO particles begin to form.